Dinamika Legitimasi Sosial dan Formal Dalam Pengelolaan Zakat: Studi Kasus Masjid At-Taqwa Marbau - Muhammad Alwi Dalimunthe; Laila Afni Rambe; Ilka Sawidri Daulay (J-Alif : Jurnal Penelitian Hukum Ekonomi Syariah dan Budaya Islam, 2026)
This study examines the dynamics of social and formal legitimacy in zakat management at Masjid At-Taqwa Marbau, focusing on local committees operating without formal administrative recognition. The academic problem addressed is how social legitimacy is formed and interacts with fiqh principles and formal regulations, as well as its implications for the sustainability of zakat management. The study employs a qualitative case study approach, involving in-depth interviews, participatory observation, and documentation, with data analyzed using Huberman and Miles’ interactive analysis model. Findings indicate that community-based zakat management operates temporarily and informally, emphasizing efficiency, procedural simplicity, and social harmony. Social legitimacy is established through trust, tradition, social proximity, and informal religious authority, often serving as the primary foundation for the practice’s success. Tensions arise when social legitimacy intersects with formal legal requirements and fiqh principles, particularly regarding accountability, distribution, and the status of amil. This study proposes a hybrid legitimacy model, integrating the strengths of social legitimacy with formal governance principles, allowing zakat management to remain community-based while enhancing accountability and transparency. The findings contribute conceptually to understanding the relationship between social and formal legitimacy in zakat management in Indonesia.